2019
DOI: 10.3390/met9040474
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microstructure and Mechanical Properties of Stellite 6 Part Fabricated by Wire Arc Additive Manufacturing

Abstract: Stellite 6 alloy has excellent wear resistance, corrosion resistance, and oxidation resistance, however the difficulties in traditional processing limit its wide application. Additive manufacturing technology that has emerged in recent years is expected to provide a new way for the processing of stellite 6 alloy. In this study, two square thin-walled stellite 6 parts were fabricated through the wire arc additive manufacturing technology. At the same time, the effect of stress relief annealing on the mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The width of the thin walls increased from 7.5-8.0 mm to 8.5-9.0 mm after treatment UVA. The size of the WAAM component is decided by the shape of the molten pool [12]. The ultrasonic vibration is able to accelerate the relative movement between the solid phase and surrounding liquid phase in the molten pool, leading to a better spreading of the molten pool on the previously deposited layers.…”
Section: Macrostructurementioning
confidence: 99%
See 1 more Smart Citation
“…The width of the thin walls increased from 7.5-8.0 mm to 8.5-9.0 mm after treatment UVA. The size of the WAAM component is decided by the shape of the molten pool [12]. The ultrasonic vibration is able to accelerate the relative movement between the solid phase and surrounding liquid phase in the molten pool, leading to a better spreading of the molten pool on the previously deposited layers.…”
Section: Macrostructurementioning
confidence: 99%
“…In recent years, wire arc additive manufacturing (WAAM) has gained considerable interest due to its high deposition rate, efficiency, full density, and low equipment cost [10]. In WAAM process, an electric arc is used as a heat source and employs either gas metal arc welding (GMAW [11]), gas tungsten arc welding (GTAW [12]) or plasma arc welding (PAW [13]) to melt the wire as the feed stock. As compared to the conventional casting, the cooling rates in WAAM are significantly higher (WAAM: 10 2 K/s [14], cast: 10K/s [6]) to obtain fine grains.…”
Section: Introductionmentioning
confidence: 99%
“…Stellite 6 parts manufactured by wire arc additive manufacturing (WAAM) exhibit good formation quality. The parts manufactured by WAAM can be made thinner than the cast parts [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LENS technique has been successfully used for the application of multi-layer Stellite™ coating on stainless steel for use on cutting tools [ 43 ]. However, as the authors of [ 44 ] have indicated, there are very few papers on the fabrication of Stellite 6 alloy parts using additive techniques. Recently, Traxel and Bandyopadhyay [ 22 ] have successfully obtained WC-Co + diamond composites using the LENS technique.…”
Section: Introductionmentioning
confidence: 99%